KINERJA PENGELOLAAN KEARSIPAN PADA UPT LAYANAN KEPENDIDIKAN KECAMATAN ANGGANA - Sri Wahyuni (ADMINISTRASI PUBLIK, 2020)
This study was conducted to describe the actual state of archival management performance and to find and describe the supporting and inhibiting factors of archival management performance at the Technical Executive Unit of Education Service of Anggana District.This research is in qualitative descriptive format with primary data needed is the experience of the archives manager and the activities of archival management. Several factors were found to be inhibiting and supporting the performance of archival management at the Anggana District Education Service Office. Namely personal factors, leadership factors, team factors and system factors. The supporting factors of archival management performance in the Anggana District Education Services office are found in contextual or situational factors. Because financing problems are a dimension that influences other dimensions of performance, it is necessary to allocate budgeting records in a controlled manner with regard to other costs that support management financing.